Disparities in Community Food Environments - Alicia Papanek; Catherine G. Campbell; Karla Shelnutt (EDIS, 2023)
This publication reviews types of food environment disparities and their implications for food and nutrition security. Written by Alicia Papanek, Catherine G. Campbell, and Karla Shelnutt, and published by the UF/IFAS Department of Family, Youth and Community Sciences, May 2023.